Pengaruh Employee Engagement terhadap Turnover Intention Studi Kasus PT XYZ Bandung - Nida Kania Fauzia; Marwansyah (Jurnal Riset Bisnis dan Investasi, 2020)
This research aims to know the level of employee engagement, turnover intention, and influence employee engagement against turnover intention. The methods used in this research is descriptive statistical analysis, while the techniques of data collection using the questionnaire as a primary data and international journals as well as books as the secondary data. Based on the results of the research that has been done, the regression equation is Y = 68,179-0,215X. The results showed that there were negative and significant influence between employee engagement and turnover intention is amount -0.215 and employee engagement affect turnover intention is amount 7.8%.